2020
DOI: 10.1159/000507553
|View full text |Cite
|
Sign up to set email alerts
|

The Thromboelastographic Profile at Birth in Very Preterm Newborns with Patent Ductus Arteriosus

Abstract: Background: The role of hemostasis in the closure of patent ductus arteriosus (PDA) in preterm infants is controversial. Objective: To assess thromboelastography (TEG) at birth in very-low-birth-weight (VLBW) infants affected by PDA. Methods: This was an ancillary study of a prospective observational study aimed at defining the TEG profile in healthy VLBW infants in the first month of life. In this analysis, we included neonates of < 33 weeks' gestational age (GA) with PDA and compared TEG traces based on (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The new search identified 20 articles (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) that were added to the 11 already included in our previous meta-analysis (19). The PRISMA flow diagram of the search process is shown in Supplementary Figure 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…The new search identified 20 articles (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) that were added to the 11 already included in our previous meta-analysis (19). The PRISMA flow diagram of the search process is shown in Supplementary Figure 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…In pediatric cardio surgery, viscoelastic assays proved to optimize blood product use while reducing bleeding [28]. In the neonatal setting, viscoelastic tests have been used to evaluate neonates with bleeding, sepsis, and patent ductus arteriosus under pharmacological treatment [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…ADP, adenosine di-phosphate; GPIIb/IIIa, glycoprotein IIb/IIIa; PAC-1, procaspase activating compound 1 which detects activated GPIIb/IIIa. medical treatment exhibited signs of an enhanced fibrinolysis (46). While the exact mechanisms and the clinical consequences of these findings are yet to be examined, they further indicate a role of the neonatal coagulation system in ductal closure.…”
Section: Platelet Function and Pda Closure In Preterm Infantsmentioning
confidence: 92%
“…Recently, other investigators found lower PDGF levels in very immature infants (22-27 weeks) with failure of spontaneous DA closure (45). In addition, Ghirardello et al (46) assessed thromboelastography at birth in VLBW infants with PDA (n = 151). In their study, thromboelastography at birth did not predict persistence of PDA.…”
Section: Platelet Function and Pda Closure In Preterm Infantsmentioning
confidence: 99%